Enhancing the utilization of rapeseed protein ingredients in bread making by tailored lactic acid fermentation. (December 2022) - Wang, Yaqin; Rosa-Sibakov, Natalia; Edelmann, Minnamari; Sozer, Nesli; Katina, Kati; Coda, Rossana
Abstract: The aim of this study was to investigate the performance of rapeseed protein isolate (RPI) or concentrate (RPC) as such and after lactic acid bacteria fermentation as ingredients in composite wheat baking. Bread recipes were developed replacing wheat flour with RPI (10%) or RPC (20%) to obtain a high protein bread. Fermentation of the rapeseed protein ingredients with Weissella confusa A16 enabling synthesis in situ of dextran contributed to obtaining bread with improved textural properties. The in situ produced dextran in RPI (6.1% dry matter) and RPC (5.7% dm) increased the bread specific volume (10% and 14%, respectively) and decreased crumb hardness (35% and 25%, respectively) compared to the respective control breads. Furthermore, fermentation of RPC significantly improved the free amino acid profiles e.g., lysine, methionine, and isoleucine, which are deficient in wheat bread. Protein digestibility in vitro was significantly enhanced in the breads containing fermented RPI, but not in the one with fermented RPC, probably due to the higher level of condensed tannins in RPC after fermentation.